(untitled) (Eastern Librarian, 2012)
Public libraries are very important social organizations in building knowledge based society. There are two types of public libraries in Bangladesh i.e. Government public libraries and Non-Government public libraries. This article concentrates on the status of Non-Government public libraries in Bangladesh. There is very few literature on Non-Government public libraries in Bangladesh. Currently there are 972 Non-Government public libraries running in Bangladesh. In gathering data on Non-Government public libraries in Bangladesh, the Directory of Non-Government Public Libraries published by National Book Centre is considered. A Focus Group Discussion (FGD) has been conducted to acquire comprehensive information about the status of Non-Government public libraries in Bangladesh. Eventually some problems of Non-Government public libraries have been addressed and as remedial measures a number of recommendations have been put forward by the authors. DOI: http://dx.doi.org/10.3329/el.v23i1.12119 Eastern Librarian Vol.23(1) 2012 pp.91-104